Simple Rule Editor for the Internet of Things - Tuomisto, Timo; Kymalainen, Tiina; Plomp, Johan; Haapasalo, Anu; Hakala, Kati (2014 International Conference on Intelligent Environments, 2014)
This paper proposes a 'Thing'-centric simple rule editor for the Internet of Things. The demonstration is aimed at laymen to connect and configure sensors and their home appliances. In providing a tool for simple do-it-yourself configurations, we present a user-centric approach for the combining and configuring of tasks that can be deployed in highly diverse domestic contexts, with heterogeneous resources available and with deployment environments changing over time. Composing and configuring the tasks of the sensors and devices take center stage in our 'Thing' - or object-centric prototype. An important part of the user-centric editing tool is the visualization scheme for the graphical representation of the heterogeneous sensors and devices, combined with verbal instructions for editing.